The Myth of Kaomu in Local Election of Muna Regency: The Politic of Language and the Emergence of Local Oligarchy - Bilu, La; Rasiah, Rasiah (Universitas Muhammadiyah Malang, 2025)
This research examines kaomu as a political myth that continues to be reproduced in the post-reformation era in Muna Regency, Southeast Sulawesi, Indonesia. Kaomu is a group of people who have been narrated as leaders since the beginning of the founding of the Muna kingdom. It is produced as a political myth in era of Muna ancient kingdom and reproduced through language politics until the post-reformation era in Indonesia. As a result, the descendants of the Kaomu group have received social and cultural legitimacy to be chosen as leaders compared to other candidates; Walaka or Maradika social classes. Data was collected through historical documents, oral traditions, and interviews. This study suggested that kaomu myth in the post-reformation era on regional elections has become an instrument of political power in Muna. The myth of kaomu as collective knowledge directs society to elect someone based on a knowledge regime that has been established for hundreds of years. On the other hand, candidates from the kaomu group are also increasingly develop their capital not only in political arena but also economic and sociocultural ones. By this way, their existence is strengthened both in the party and in strategic positions in the local and national axis.